The short-term effects of ORKAMBI (lumacaftor/ivacaftor) on regional and distal lung structures using functional respiratory imaging. (September 2021) - Lauwers, Eline; Belmans, Dennis; Mignot, Benjamin; Ides, Kris; Van Hoorenbeeck, Kim; Snoeckx, Annemiek; Van Holsbeke, Cedric; Nowé, Vicky; Van Braeckel, Eva; De Backer, Wilfried; De Backer, Jan; Verhulst, Stijn
Background: Lumacaftor/ivacaftor (LUM/IVA) has shown modest benefits in previous research, but the exact effects in the cystic fibrosis (CF) lung remain unclear. This study aims to offer novel information on the mode of action of the cystic fibrosis transmembrane conductance regulator (CFTR)-modulating drug by assessing lung structure and function using functional respiratory imaging (FRI). Methods: CF patients aged ⩾12 years homozygous for F508del were recruited in an open-label study. Before and after 12 weeks of treatment with LUM/IVA, FRI was used to visualize regional information, such as air trapping, lobar volume and airway wall volume. Secondary outcomes included the CF-CT scoring system, spirometry, the Cystic Fibrosis Questionnaire–Revised (CFQ-R) questionnaire, exercise tolerance and nutritional status. Results: Of the 12 patients enrolled in the study, 11 completed all study visits. Concerning the FRI parameters, hyperinflation of the lung decreased, indicated by a reduction in air trapping and lobar volume at expiration. Also, a decrease in airway wall volume and a redistribution of pulmonary blood volume were noted, which might be related to a decrease in mucus impaction. Airway resistance, airway volume, internal airflow distribution and aerosol deposition pattern did not show significant changes. No significant improvements were found in any of the CF-CT scores or in the spirometric parameters. Other secondary outcomes showed similar results compared with previous research. Correlations at baseline were found between FRI and conventional outcomes, including physical functioning, spirometry and CF-CT scores. Conclusions: LUM/IVA decreased lung hyperinflation in combination with a potential decrease in mucus impaction, which can be related to an improved mucociliary transport. These results indicate that several FRI parameters, reflecting regional and distal lung structures, are more sensitive to changes caused by LUM/IVA than conventional respiratory outcomes.